Surface defects of BGO crystals - Galenin, E.P.; Gerasymov, I.V.; Nahornyak, V.T.; Sidletskiy, O.Ts.; Tkachenko, S.A. (Functional Materials, 2008)
The surface defects of Bi₄Ge₃O₁₂ crystals grown by Czochralski have been considered. The influence of the melt level lowering in the crucible and the growth atmosphere composition on the formation of defects have been described. A mechanism of defect formation has been proposed making in possible to judge of the crystallization front stability and morphology during the crystal growth and the presence of blocks in the crystals basing on the observed defect character. Розглянуто поверхневі дефекти кристалів Bi₄Ge₃O₁₂, вирощених методом Чохральського. Описано вплив зменшення рівню розплаву у тиглі й складу середовища вирощування на утворення дефектів. Запропоновано механізм їх виникнення, який дає можливість за характером дефектів оцінювати морфологію і стабільність фронту кристалізації під час росту кристала, наявність блоків у кристалах. Рассмотрены поверхностные дефекты кристаллов Bi₄Ge₃O₁₂, выращенных классическим методом Чохральского. Описано влияние уменьшения уровня расплава в тигле и состава среды выращивания на образование дефектов. Предложен механизм их возникновения, позволяющий по характеру дефектов судить о морфологии и стабильности фронта кристаллизации во время роста кристалла, размерах ячеек и наличии блоков в кристаллах.